Pengaruh Tunneling Incentive, Intangible Asset, Dan Debt Covenant Terhadap Keputusan Transfer Pricing Dengan Tax Minimization Sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2021) - Azka Aminah Azzuhriyyah; Kurnia Kurnia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of tunneling incentives, intangible assets, and debt covenants on transfer pricing with tax minimization as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2021 period. The population in this study are manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2021. The sample selection technique used is purposive sampling and obtained 18 samples of companies with a research period of 7 years in order to obtain a total of 126 research observations. The data used in this financial research is obtained from company report data. The data analysis method in this study is logistic regression analysis and moderate regression analysis which was tested with SPSS 26 software. . Partially, debt covenants have a positive effect on transfer pricing. Meanwhile, tunneling incentives and intangible assets have no effect on transfer pricing decisions for manufacturing companies listed on the Indonesia Stock Exchange in 2015-2021.